2005
DOI: 10.1007/s00423-005-0577-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lateral pelvic lymph node dissection on evacuatory and urinary functions following low anterior resection for advanced rectal carcinoma

Abstract: Although LPLD affected urinary dysfunction, it did not impair postoperative evacuatory function in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 33 publications
(45 reference statements)
1
32
0
Order By: Relevance
“…5 Some investigators have reported that more extensive surgery does not seem to increase the incidence of PUR. 2,10,24,25 According to these reports, both conventional rectal cancer surgery and more extensive and radical procedures have a similarly favorable outcome with respect to bladder function. 2,10 Several reports on pelvic autonomic nerve preservation have demonstrated a lower incidence of urinary dysfunction after rectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5 Some investigators have reported that more extensive surgery does not seem to increase the incidence of PUR. 2,10,24,25 According to these reports, both conventional rectal cancer surgery and more extensive and radical procedures have a similarly favorable outcome with respect to bladder function. 2,10 Several reports on pelvic autonomic nerve preservation have demonstrated a lower incidence of urinary dysfunction after rectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, lateral pelvic lymphadenectomy is routinely performed for patients with advanced low rectal cancer, whereas it is not frequently performed in the Western countries [26][27][28] . In the current study, a retrospective analysis was performed in 96 patients with advanced low rectal cancer who underwent curative surgery with lateral lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The terminology has varied considerably, with no universal consensus. Table 1 outlines the published terminology and abbreviations, where given33, 39, 45–65. Initially, lateral side‐wall lymphadenectomy was associated with para‐aortic lymphadenectomy.…”
Section: Early Reports and Development Of Lateral Pelvic Lymphadenectomymentioning
confidence: 99%